Enabling Self-Organization in Embedded Systems with Reconfigurable Hardware - Christophe Bobda; Kevin Cheng; Felix Mühlbauer; Klaus Drechsler; Jan Schulte; Dominik Murr; Camel Tanougast (International Journal of Reconfigurable Computing)
We present a methodology based on self-organization to manage resources in networked embedded systems based on reconfigurable hardware. Two points are detailed in this paper, the monitoring system used to analyse the system and the Local Marketplaces Global Symbiosis (LMGS) concept defined for self-organization of dynamically reconfigurable nodes.